Emergent Superconductivity in Low Dimensions - Ansermet, Diane (Springer Theses, Recognizing Outstanding Ph.D. Research, 2018)
This book explores the relationship between electronic correlations, dimensionality, inhomogeneities, and superconductivity in low-dimensional systems by studying single crystals of the quasi-one-dimensional Na2-δMo6Se6, composed of MoSe filaments weakly coupled by Na atoms and subject to intrinsic disorder (δ ‰ 0). It shows that the Na2-δMo6Se6 displays strong electronic correlations in its normal state, whereas a superconducting ground state emerges from Anderson localized electrons. Two novel behaviors of the superconducting state are observed: first, a disorder induced enhancement of the superconducting transition temperature; second, a reentrant phase coherence with increasing temperature, magnetic field, and current. It also analyzes the intrinsic properties of Na2-δMo6Se6 are analyzed to offer a thorough understanding of these phenomena. The emergence of superconductivity in such low-dimensional systems provides a fruitful playground to explore electronic order and correlations.